2020
DOI: 10.1016/j.trd.2020.102562
|View full text |Cite
|
Sign up to set email alerts
|

Cycling diversity, accessibility, and equality: An analysis of cycling commuting in Bogotá

Abstract: In a context of rising awareness for environmental concerns and promotion policies targeting nonmotorized travel as a sustainable mobility solution, the bicycle has increasingly become an attractive transport mode in cities. However, accessibility to opportunities for people who cycle is not necessarily the same across socioeconomically different population segments, and it tends to be further constrained by high costs associated with the travel distance through the road network.This research examines equality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 46 publications
2
11
0
Order By: Relevance
“…This trend confirms other studies' results showing that cycling and BRT trips are mainly used for commuting to work [54]. Second, results showed that active mobility was concentrated around the central AQSs, confirming that a high centrality in cities promotes mobility concentration in the downtown area where the main economic activity is concentrated [55], as in other metropolises in Latin America [56,57].…”
Section: Discussionsupporting
confidence: 88%
“…This trend confirms other studies' results showing that cycling and BRT trips are mainly used for commuting to work [54]. Second, results showed that active mobility was concentrated around the central AQSs, confirming that a high centrality in cities promotes mobility concentration in the downtown area where the main economic activity is concentrated [55], as in other metropolises in Latin America [56,57].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, this finding shows that bicycles may be a temporary commuting option as commuters work to acquire a motorized mode of transport. In the context of the rapid growth in the ownership of motorized vehicles, school-based programs such as al Colegio en Bici (“To school by bike”) and biking programs on the Sunday Ciclovia in Bogotá might increase interest in alternative means of transport during adulthood ( Rosas-Satizábal et al, 2020 ). Regarding our finding that increasing average terrain slope is negatively associated with bicycling, previous research has also found that the probability of bicycling decreases as the terrain slope becomes steeper ( Hunt and Abraham, 2007 ; Parkin et al, 2008 ; Rietveld and Daniel, 2004 ; Rodríguez and Joo, 2004 ; Stinson and Bhat, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Within this context, the bicycle becomes a more suitable and affordable option. Additionally, middle- and higher-SES men may not be interested in bicycle commuting as they are no longer budget-constrained to using public transport and might gain access to alternative transport modes, such as motorized vehicles, with a better personal cost-benefit ratio compared to bicycling ( Gómez-Gélvez and Obando, 2014 ; Rosas-Satizábal et al, 2020 ). The motivation for bicycle commuting among those in higher socio-economic groups might come from environmental awareness strategies as discussed by Rodriguez-Valencia, et al ( Rodriguez-Valencia et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations